Young women, health and physical activity: tensions between the gendered fields of Physical Education and Instagram. Issue 7 (2nd September 2022) - Camacho-Miñano, Maria José; Gray, Shirley; Sandford, Rachel; MacIsaac, Sarah
ABSTRACT: Drawing on the conceptual frameworks of Bourdieu and postfeminism, this article analyses extant tensions between young women's gendered habitus and the health-related learning spaces of Physical Education (PE) and Instagram. We draw on data from a two-phase qualitative research project with thirty-seven young women (aged 15–17) from three secondary schools in Spain who self-defined as physically active and engaging with exercise content on Instagram. Data obtained through focus groups and semi-structured interviews reveal how these young women's subjectivities are formed through negotiating the gender 'rules of the game' within these key pedagogical fields. Notably, most participants were critical of their learning in PE, which mainly remains a traditional masculine field. By contrast, they valued Instagram as an engaging space in which to learn about fitness to transform their bodies toward the feminine ideal. This involved a constant process of self-optimization, including the development of the 'right' mental dispositions, fitting strongly with their gendered habitus. Within this paper, we have developed the concept of 'postfeminist habitus' to explain the participants' engagements with health-related content on Instagram, which through language of choice and empowerment, disciplined the young women to achieve the normative body as a marker of success. We argue that while there are notably different patterns of engagement with PE and Instagram, in both spaces there is evidence of symbolic violence that reproduces the gender order. We conclude by suggesting changes that might make PE a more meaningful and hybrid learning space for young women.